A Netnographic Study of Identity, Acculturative Stress, and Transnational Grief Among the Diaspora - Nurul Huda; Esa Rosyida Umam; Nurul Fahmi Rizka Laily; Salwa Al Eryani (Interdisciplinary Journal of Ethnopsychiatric Nursing, 2026)
Background: International migration exposes diaspora populations to a distinctive constellation of psychological stressors, including acculturative friction, identity renegotiation, and disrupted mourning, that host-country psychiatric services rarely address in culturally congruent ways. Gap: Digital communities have become a primary site where diaspora members process these stressors, yet qualitative evidence describing how such platforms function as informal psychosocial infrastructure remains scarce, particularly for Southeast Asian diaspora populations. This study examined how global Indonesian diaspora communities construct cultural identity, negotiate acculturative stress, and manage transnational grief within digital spaces, with attention to implications for psychiatric nursing practice. Methods: A 22-week netnographic observation was conducted across transnational Facebook groups, Reddit communities, Discord servers, and WhatsApp networks, capturing publicly archived discussion threads analysed thematically in accordance with Standards for Reporting Qualitative Research (SRQR) guidance. Results: Four interrelated themes emerged: digital homeland and cultural anchoring; acculturative stress and the in-between identity; collective digital resilience and peer support; and transnational grief and intergenerational trauma. Diaspora members used online spaces to rehearse cultural practices, informally broker encounters with foreign healthcare systems, and mourn losses they could not physically attend. Conclusion: Digital diaspora communities represent an underrecognised psychosocial resource; psychiatric nursing should engage with them directly through culturally responsive assessment and cross-sector partnership, rather than treating online help-seeking as a proxy for formal care.